IMPLEMENTASI TEKNOLOGI TEPAT GUNA SOLAR DYER HOUSE DAN PENINGKATAN MUTU DAN NILAI TAMBAH KOPI RAKYAT DI DESA SUANAE - Wolfrit Matoneng, Ody; M. P. Keraf, Fransiskus; Peter Gellu, Leonard; V. Feka, Gonsianus Pakaenoni, Wolfhardus; Yuniti, I Gusti Ayu Diah; Putu Sukanteri, Ni; Yuesti, Anik (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2025)
Suanae Village, North Central Timor Regency, is one of the centers of smallholder coffee farming with great potential for coffee agribusiness development. However, the post-harvest process of coffee in this village still faces various obstacles, especially in drying coffee beans and utilizing coffee husk waste. This community service research aims to improve the quality and added value of smallholder coffee through the implementation of appropriate technology, namely Solar Dryer Houses (SDH) and the processing of coffee husk waste into organic fertilizer. The activity methods use a participatory and collaborative approach, including socialization, training, mentoring, as well as monitoring and evaluation. The results of the activities show an average increase of 80% in farmers' knowledge and skills, a reduction in coffee bean drying time from 7-10 days to 3-5 days, and an increase in the selling price of dried coffee by 10-15% which was previously purchased at an estimated price by collectors of 30,000, but with the solar dyer house technology, coffee farmers hope to get a price of more than Rp. 39,000. In addition, coffee husk waste is utilized as solid organic fertilizer that supports sustainable agriculture and opens up additional business opportunities for the community. The implementation of this technology emphasizes the importance of local-based innovation to increase productivity, product quality, and community empowerment in rural areas.